Implementation of IoT-Based Smart Tourism Destination Tools as Tourism Leisure 5.0 - Chan, Andi Supriadi; Destiadi, Rezha; Hasibuan, Annalisa Sonaria; Aranski, Alvendo Wahyu; Ardiansyah, Luky (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Due to its ability to create commercial opportunities that local communities can manage, tourism is a well-known industry with significant development potential. Information technology has had significant advancements in its application within the tourism industry, and its implementation is now commencing in Indonesia. The use of IoT technology in the tourism industry necessitates a series of sequential stages, culminating in the establishment of a comprehensive information platform that facilitates the monitoring and administration of tourism activities. Utilizing IoT technology to construct a tourist platform helps expedite the process of integrating information and infrastructure while effectively leveraging smart technology in the tourism sector. The research methodology employed is a hybrid approach. The data outputs are processed and evaluated using a strategy that caters to the interests of the community and parties involved in the collaborative development of smart tourism, both qualitatively and quantitatively. The analysis stage uses the theory of visual perception as a way to understand what the desired implementation of IoT-based smart tourism looks like. This is shown in the selection stage. Meanwhile, this investigation concluded with a technological readiness level of five. The research was conducted without any prior investigation that aligned with the themes, tools, and objects employed by the researchers, representing the current state of the art. Furthermore, the research team comprises specialists in the domain of information systems, including two members who possess expertise in information systems and languages. This ensures a comprehensive grasp of the tools utilized in model development, collaboration, and the potential for technological advancement. In addition to the desired outcome, this is an Internet of Things (IoT)-based intelligent tourism system that may be utilized as a tool in many tourist destinations across Indonesia.